Empty Sovereignty and Public Power: Critique of Political Economy and the Political Character of Economic Laws - Carlino, Fabrizio (Sofia, 2023)
This article discusses the hypothesis that what articulates mere economic 'facts' as if they were non-political relations, is still the exercise of political power; and that, consequently, the apparent 'legal vacuum' of the state of exception understood as 'meaningless vigour', in Giorgio Agamben's terminology, is nothing more than the mystified form in which the political character of economic laws is expressed today. An attempt is thus made to test the resilience of this relationship, between economics and politics, in the light of the dialectic between act and power, captured through the critique of their separation, on which the operaist conception of the Marxian critique of political economy rests. Operaism is not only summoned here because it is able to provide adequate historical material for the critique of the concepts it intends to propose; the evolutions of the thought of Antonio Negri and Mario Tronti, in particular, are paradigmatic of the dual process of autonomisation of the actuality and potentiality of political subjectivity, respectively, which operaism has sustained by resorting to the categories of political theology.
Keywords: Mario Tronti; public power; empty sovereignty; critique of political economy